2003
DOI: 10.1002/ldr.572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use on soil erosion and nitrogen loss in the hilly area of the Loess Plateau, China

Abstract: SUMMARYThe study focused on the so-called dark coniferous forest belt on the northern slope of Changbai Mountain, at an altitude of 1100 to 1700 m. Forty tree species, 50 shrub species and 165 herb species were recorded in a series of transects. The main impact factors on forest diversity and proposals for sustainable management of this diversity were studied using an altitude and area gradient pattern method. The results showed that the diversity of dark coniferous forest gradually decreased from lower to upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 14 publications
0
55
2
Order By: Relevance
“…We have found that land uses have effects on runoff and erosion soil, and the observed data in this study period (Tables 1 and 2) could show the processes of soil erosion and N loss from different land uses in this region (Fu et al 2004). In this paper we will discuss the effects of land use on P loss.…”
Section: Resultsmentioning
confidence: 67%
“…We have found that land uses have effects on runoff and erosion soil, and the observed data in this study period (Tables 1 and 2) could show the processes of soil erosion and N loss from different land uses in this region (Fu et al 2004). In this paper we will discuss the effects of land use on P loss.…”
Section: Resultsmentioning
confidence: 67%
“…1). Prior studies showed that chemical fertilizers applied to cropland in largeslope watersheds can be readily eroded or leached out to rivers (Yavtushenko et al 1999;Fu et al 2004;Teixeira and Misra 2005). Additionally, the main types of bed rock in this region are carbonate rock 1958 1962 1966 1970 1974 1978 1982 and alkaline purple shale (China Physical Geography Edit Committee 1981), and the pore water of soils derived from these types of rocks generally has a high pH (Li et al 1978;Xi and Xu 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The problems of soil erosion and environmental degradation resulting from long-term anthropogenic influences and the inherent vulnerability of the Chinese Loess Plateau have always been of deep concern to relevant government departments and academic institutions (Xu et al 2009). In recent years, much work has been done on soil erosion assessment at plot or catchment scale (Kang et al 2001;Fu et al 2004), and some at regional scale (Yang et al 2002;Fu et al 2005). However, the quantitative assessment of spatially distributed soil erosion has not been adequately addressed, and more work should be done on this topic.…”
Section: Introductionmentioning
confidence: 99%